Ectopic RASGRP2 (CalDAG-GEFI) expression in rheumatoid synovium contributes to the development of destructive arthritis. Issue 12 (3rd August 2018) - Nakamura, Hiroyuki; Shimamura, Sanae; Yasuda, Shinsuke; Kono, Michihito; Kono, Michihiro; Fujieda, Yuichiro; Kato, Masaru; Oku, Kenji; Bohgaki, Toshiyuki; Shimizu, Tomohiro; Iwasaki, Norimasa; Atsumi, Tatsuya
Abstract : Objectives: Rheumatoid arthritis (RA) is an autoimmune polyarthritis, in which fibroblast-like synoviocytes (FLS) play a key role in cartilage and bone destruction through tumour-like proliferation and invasiveness. Considering still unsatisfactory remission rate in RA even under treatment with biological disease-modifying antirheumatic drugs, novel therapeutic strategy for treatment-resistant RA is still awaited. In this study, we analysed the expression and function of Ras guanine nucleotide-releasing proteins (RASGRPs), guanine exchange factors for small GTPase Ras, in FLS as a potential therapeutic target for RA. Methods: The expression of RASGRPs mRNA was quantified by a real-time PCR assay in FLS isolated from synovial tissue samples. RASGRP2 protein was also evaluated immunohistochemically. Then, we transiently transfected FLS with RASGRP2 expression vector and assessed their proliferation, adhesion, migration and invasion by cellular functional assays and downstream signalling activation using immunoblot. Finally, the therapeutic effect of RASGRP2 silencing was evaluated in type-II collagen-induced arthritis rats. Results: RASGRP2 was abundantly expressed in FLS from RA synovium, whereas scarcely found in those from osteoarthritis. Expression of RASGRP2 in RA-FLS was enhanced by transforming growth factor-beta. RASGRP2 activated RAP-1, subsequently affecting nuclear factor kappa-light-chain-enhancer of activated B cells pathway and actin dynamics in FLS. RASGRP2-overexpressed FLS had increased abilities of adhesion, migration and interleukin (IL)-6 production. Silencing of RASGRP2 using the intra-articular injection of Rasgrp2 -specific siRNAs dampened experimental arthritis in rats by inhibiting pannus formation. Conclusions: RASGRP2 was identified to be involved in the pathogenesis of RA by promoting adhesion, migration and IL-6 production from FLS, proposed as a potential novel non-immunosuppressive therapeutic target for RA.